An observation on inappropriate probiotic subgroup classifications in the meta-analysis by Lau and Chamberlain - McFarl; LV (International Journal of General Medicine, 2016)
Lynne V McFarland Department of Medicinal Chemistry, University of Washington, Seattle, WA, USA I read with great interest the systematic review of meta-analysis assessing probiotics for the prevention of Clostridium difficile-associated diarrhea (CDAD) published in the International Journal of General Medicine. These authors pooled 26 randomized controlled trials (RCTs) and concluded that Lactobacilli, mixtures, and Saccharomyces probiotics were effective in preventing CDAD. However, the meta-analysis by Lau and Chamberlain is flawed due to improper classification by the types of probiotics. It is important to recognize that the efficacy of probiotics for various diseases has been shown to be strain specific for each probiotic product, and thus the data should only be pooled for probiotics that are of the identical type. In their analysis of probiotic subgroups by various species, the authors have inappropriately merged different types of Lactobacilli into one subgroup “Lactobacilli” and different types of mixtures into one group classified as “Mix”.View the original paper by Lau and Chamberlain.